INVESTIGATION OF SNOW THAWING USING RADIOACTIVE ISOTOPES - Agashkin,Yu. N. (1970)
Study of the influence of agrotechnical measures on runoff is one of the themes on which experimental work is being done for study of slope runoff in special runoff areas and drainage gullies. In the investigations of the course of springtime snow thawing, as one of the factors involved in runoff, a method was used which made it possible to study this process without disrupting its natural course, which is inevitable when using an instrument based on the snow-weighing principle. This requirement now is satisfied best by use of the radioactive isotopes method. Using this method it is possible with sufficient accuracy to study the change of the water reserves in the snow at the time of thawing, tracing its diurnal variation on different underlying surfaces and under different conditions (forest, glade, open plowed land). (Author) Trans. of Akademiya Nauk SSSR. Izvestiya. Seriya Geograficheskaya, n4 p117-121 1960.